Impact of working capital ratios on profitability in selected four-wheeler automobile companies - Rahman, Abdul (The Lumbini Journal of Business and Economics, 2023)
Purpose: The purpose of this study is to assess whether or not working capital ratios have an impact on the profitability of selected four-wheeler automobile companies. Design/methodology/approach: To assess the working capital management ratios on profitability in selected four-wheel automobile companies, the author applied the coefficient of correlation, correlation matrix, and multiple regression analysis methodology in selected four-wheel automobile companies listed on the CMIE prowess and secondary data considered also in annual reports. Ten passenger car manufacturing companies were selected for the period between 2011–12 to 2020–21, to choose a sample from the universe for research purposes., the purposive (judgmental) selection method is preferred for secondary data. Six different working capital component ratios (current ratio (CR), liquidity ratio (LR) are moderate ratios, working capital turnover ratio (WCTR), inventory turnover ratio (ITR), receivables turnover ratio (RTR), and cash turnover ratio (CTR)) are independent ratios have been measured for their impact on profitability using the coefficient of correlation and regression. Profit before tax to asset ratio (PBT/Total assets (dependent ratio). Findings: The study found that Working capital ratios (CR, QR, WCTR, ITR, RTR, and CTR) are positively correlated with profitability ratios. Of the six working capital component ratios, five of them are significant at a 5-percentage level, except cash turnover ratios. Contribution/Originality: Managers at four-wheeler companies need to improve the efficiency and effectiveness of the firm's financial management to avoid working capital ratios that put the company in jeopardy. To help with investing decisions, it may be used as a benchmark of firms who have demonstrated strong financial success.